Trailblazers in STEM: a document analysis of the accomplishments of Louis Stokes Alliances for Minority Participation alumni - Smart Graham, Dominique; Crawford, Meli'sa S.; Chicas-Mosier, Ana M. (Frontiers in Education, 2025)
The National Science Foundation (NSF) Louis Stokes Alliance for Minority Participation (LSAMP) has a > 30-year history of providing high impact educational experiences to undergraduates and graduate students of color in science, technology, engineering, and mathematics (STEM). In 2020, LSAMP program leadership published biographical information from 1,137 alumni across 36 alliances. In this article, data were extracted from that publication and analyzed by major discipline, listed degrees earned, and alliance affiliation. Doctoral recipient data were compared to the National Center for Science and Engineering Statistics Survey of Earned Doctorates data between 1992 and 2022. Key findings were that the LSAMP program has supported at least 6% of doctorates earned by people of color (POC) in STEM fields since its inception. When disaggregated by discipline, 12 and 10% respectively, of doctorates earned by POC in mathematics and computer science and physical and earth sciences were LSAMP alumni. We identify factors contributing to variation between alliances in discipline and Trailblazer representation. We conclude that the LSAMP program has made a demonstrable impact on graduate degree earnings by POC since its start and suggest strategic recruitment and retention efforts based on specific alliance strengths. Continued congressional financial support of this program is pivotal to continue broadening participation in the STEM workforce.